SARS-CoV-2 Nosocomial Outbreak in Campinas City, Brazil - DA, Toledo-Teixeira; LS, Mofatto; ET, Mendes; MR, Amorim; PP, Barbosa; WO, Bragança; PL, Parise; K, Bispo-dos-Santos; LGO, Cardoso; LF, Bachur; et al. (Archives of Clinical and Biomedical Research, 2023)
Coronavirus disease (COVID-19) caused by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a cause of concern in the hospital environment due to nosocomial transmission among healthcare workers (HCWs) and patients. During the first pandemic wave worldwide, the shortage of personal protective equipment, lack of guidance to manage COVID-19 patients and the rapid spread of the virus were great contributors to nosocomial infections. From May to June 2020 in a tertiary hospital in the city of Campinas, Brazil, we identified an increasing number of HCWs infected by SARS-CoV-2 in wards not intended for the care of COVID-19 patients, which lead us to strengthen nonpharmaceutical interventions to control the virus’s spread. Here we aimed to characterize the occurrence of a nosocomial outbreak in a tertiary reference hospital in Campinas city, Brazil. For this, we combined epidemiological data, universal diagnostic testing and genomic sequencing to define the cluster of infection. We found a proportional rate among total HCWs and infected HCWs, which patient care assistants are the most frequent infected HCWs. We have also shown that epidemiological data, universal diagnostic testing and genomic sequencing as a rapid response managed to characterize a cluster of nosocomial transmission, which allowed us to establish procedures in hospital wards. Our study reinforces the importance of epidemiological and genomic surveillance for the control of SARS-CoV-2’s nosocomial transmission in reference hospitals.